Pengaruh William Flexion Exercise (Modification) terhadap Kualitas Tidur pada Kondisi Low Back Pain di Posyandu Kartini Salatiga - Kurniasari, Mita; Hastuti, Lis Sarwi (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Low Back Pain is a condition of discomfort in the form of pain in the lower back and often spreads to the legs. Lower back pain can affect sleep quality, resulting in a decrease in a person's sleep quality. Sleep quality is a person's satisfaction with sleep, reduced sleep quality affects the individual's physical and psychological condition. One non-pharmacological therapy that is useful for reducing pain and improving sleep quality is the William Flexion Exercise (Modification). Objectives: This study aims to determine the effect of the William Flexion Exercise (Modification) on sleep quality in Low Back Pain conditions at the Kartini Posyandu Salatiga. Methods: This study is a quantitative study using a quasi-experimental design method non-random pretest-posttest with control group. The sample size was 30 people and the intervention was carried out 10 sessions. Hypothesis testing used the Independent t-test. The instrument used to measure sleep quality is the Pittsburg Quality Index (PSQI). Results: The results of the parametric paired t-test of the PSQI value obtained a value of 0.01 (Pvalue <0.05) which indicates that there is a difference in the PSQI value before and after the intervention. The results of the independent t-test hypothesis test of the PSQI instrument score in this study obtained a sig value of 0.001 (Pvalue <0.05) which means that there is a significant difference in the sleep quality value between the treatment and control groups after being given the William Flexion Exercise (Modification) intervention. Conclusion: The results of this study indicate that the William Flexion Exercise (Modification) intervention has an effect on improving sleep quality in Low Back Pain conditions at the Kartini Elderly Posyandu Salatiga. Keywords: Low Back Pain, William Flexion Exercise (Modification), Sleep Quality